Validación comparada de la prueba rápida SD bioline dengue duo con el método Gold Stándar (pcr-tiempo real), para el diagnóstico de dengue en fase febril en muestras procedentes de la Región La Libertad 2017 - Rodriguez Guzman, Alexis Martín. (2019)
The need to reduce the time of diagnosis, the easy handling of its process, the use of sophisticated equipment and the reliability of this subject. The objective of this study is to compare the validation of the results of the SD Bioline Dengue Duo rapid tests with the Gold Standard method (Real-Time PCR), for the diagnosis of dengue in the February phase in the responses of the La Libertad Region 2017.It is necessary to have the level of care data, with a diagnostic method that provides reliability in the results and allows to take decisions in a timely manner of vector and clinical control.To measure the level of reliability, use 187 samples in the February phase (1 to 5 days after the onset of the disease), to which they were subjected to real-time PCR, and SD Bioline Dengue Duo rapid test, obtaining the following result: 44% positive (82 samples) and 56% negative (105 samples) for molecular diagnosis; and 40.6% positive (76 samples) and 59.4% negative (111 samples) for immunochromatographic diagnosis.The sensitivity of the rapid tests is 85.4% (PPV: 92.1%), showing that the total of positive results in the rapid test, the probability of being truly positive is 92.1%, the specificity of 94.3% (NPV: 89.2%) shows that the total of negative results in the rapid test, the probability of being negative is 89.2% and the results of Chi-Square equal X2cal = 121.087, a relation between the results by the rapid test and the results by the Standard Gold Method PCR- Real Time